Higher dietary insulinaemic potential is associated with increased risk of liver steatosis and fibrosis. (18th September 2021) - Zhu, Yu; Peng, Zhaohong; Lu, Yao; Li, Hairong; Zeng, Xufen; Zhang, Zhuang; Li, Xiude; Hu, Chunqiu; Hu, Anla; Zhao, Qihong; Wang, Hua; Yang, Wanshui
Abstract: Background and Aims: Hyperinsulinaemia and insulin resistance play a central role in the progression of hepatic steatosis and fibrosis, and diet can modulate insulin response. We thus hypothesised that diet with higher insulinaemic potential is associated with an increased risk of these conditions. Methods: Two empirically dietary indices for hyperinsulinaemia (EDIH) and insulin resistance (EDIR) were derived to identify food groups most predictive of fasting concentrations of C‐peptide and insulin and homeostatic model assessment for insulin resistance respectively. Hepatic steatosis and fibrosis were defined by controlled attenuation parameter and liver stiffness measurement using transient elastography (TE). Odds ratios (ORs) and 95% confidence intervals (CIs) were calculated by logistic regression. Results: Of the 4171 participants with TE examination, 1436 (age‐standardised prevalence, 33.8%) were diagnosed with steatosis, 255 (5.6%) with advanced fibrosis and 101 (2.2%) with cirrhosis. The multivariable‐adjusted ORs for participants comparing the highest to the lowest EDIH tertile were 1.17 (95% CI: 0.99‐1.39, Ptrend   =  .005) for steatosis, 1.74 (95% CI: 1.24‐2.44, Ptrend   =  .001) for advanced fibrosis and 2.05 (95% CI: 1.21‐3.46, Ptrend   =  .004) for cirrhosis. Similar associations were observed for EDIR with ORs of 1.32 (95% CI: 1.11‐1.55, Ptrend   <  .001) for steatosis and 1.43 (95% CI: 1.03‐1.99, Ptrend   =  .006) for advance fibrosis. These positive associations remained among never drinkers and individuals who were free of hepatitis B and/or C. Conclusions: Our findings suggest that hyperinsulinaemia and insulin resistance may partially underlie the influence of diet on hepatic steatosis and fibrosis, and highlight the importance of reducing or avoiding insulinaemic dietary pattern.